2021
DOI: 10.1177/24730114211000637
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Spin in the Abstracts of Systematic Reviews and Meta-analyses Covering Treatments for Achilles Tendon Ruptures

Abstract: Background: Approximately 18 in every 100 000 people have experienced a ruptured Achilles tendon. Despite the prevalence of this condition, treatment options remain contested. Hypothesis/purpose: The objective of this study was to evaluate the use of spin—reporting practices that may exaggerate benefit or minimize harm—in abstracts of systematic reviews related to Achilles tendon repair. We also evaluated whether particular study characteristics were associated with spin. Study design: Cross-sectional. Methods… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
16
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 22 publications
0
16
0
Order By: Relevance
“…While the current study reported important and relevant complications following the treatment of AATR, it failed to include certain outcomes that are also relevant to patients such as returning to sports or work, patient satisfaction scores, or other patients‐reported outcome measure [8, 29, 47]. Carr et al evaluated abstracts of systematic reviews of AATR and reported that 65.1% contained spin‐reporting practices that may exaggerate benefit or minimize harm [5]. Recognizing these limitations, this study sought to synthesize and present the outcomes from these meta‐analyses as objectively as possible.…”
Section: Discussionmentioning
confidence: 99%
“…While the current study reported important and relevant complications following the treatment of AATR, it failed to include certain outcomes that are also relevant to patients such as returning to sports or work, patient satisfaction scores, or other patients‐reported outcome measure [8, 29, 47]. Carr et al evaluated abstracts of systematic reviews of AATR and reported that 65.1% contained spin‐reporting practices that may exaggerate benefit or minimize harm [5]. Recognizing these limitations, this study sought to synthesize and present the outcomes from these meta‐analyses as objectively as possible.…”
Section: Discussionmentioning
confidence: 99%
“…After that publication, multiple studies were published on the presence of spin within systematic reviews for different treatment options, including orthopaedics. 7 , 11 , 15 , 18 , 23 , 26 Carr et al 5 published an article in Foot & Ankle Orthopaedics looking at the presence of spin within the systematic reviews of treatment options for Achilles tendon ruptures. The authors identified the presence of spin in 65% of their studies.…”
Section: Discussionmentioning
confidence: 99%
“…By following our recommendations, researchers and journals can identify spin at an early stage and be able to eliminate it by the time an article is published. 5 , 15 , 18 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have shown a high prevalence of spin in systematic reviews in orthopedic research. 37,39,40 An example of type 5 spin in Wang et al 34 is present in the conclusion of the abstract which states "the results of this metaanalysis demonstrate that interlaminar minimally invasive discectomy (ILMI) and MD are both safe and effective surgical procedures for treating LDH. Compared with MD, ILMI can shorten days in hospital, decrease the amounts of blood loss during surgery".…”
Section: Discussionmentioning
confidence: 99%